RELATIONSHIP OF PARENTING TO TEMPER TANTRUM BEHAVIOR OF CHILDREN 3-5 YEARS OLD IN PAUD MAWAR FKIP UNPATTI - Hermelina Abarua (EDU SCIENCES JOURNAL, 2020)
2019 "The Relationship of Parenting to Temper Tantrum Behavior Children 3-5 Years Old in PAUD Mawar FKIP Unpatti" Department of Education Faculty of Teacher Training and Education Faculty of Pattimura University Ambon. Tantrums (or temper tantrums) are emotional outbursts, usually associated with children or people in emotional distress, which are usually characterized by stubbornness, crying, screaming, screaming, screaming, insubordination, ranting angry, angry, resistance to efforts to calm and, in some cases, violence. Physical control can be lost, the person may not be able to remain silent, and even if the person's "goals" are fulfilled he may remain uneasy. This research was carried out at PAUD Mawar FKIP Unpatti. The purpose of the study was to determine the relationship of parenting to the incidence of temper tantrums in children aged 3-5 years in PAUD Mawar Unpatti. Research using a quantitative approach emphasizes its analysis on numerical data that is processed by statistical methods. The results of the analysis using the Chi Square statistical test with the SPSS program version 16.0 obtained Ï = 0.001 <Î± = 0.05 with a pearson count = 15.069 then H1 accepted H0 was rejected, which means there is a relationship between parenting parents with temper tantrums in preschool age children (3-5 Years) in Mawar PAUD FKIP Unpatti with a correlation of 0.501 which is interpreted that the strength of the relationship between variables is at a moderate level. 31 respondents in PAUD Mawar FKIP Unpatti showed that parenting in the Poor category was 10 respondents (32.46%) and 21 respondents (67.74%) had good parenting. Data of 31 respondents in PAUD Mawar FKIP Unpatti showed 15 respondents (48.38%) showed high temper tantrums, 10 respondents (32.25%) showed moderate temper tantrums, and 6 respondents (19.35%) showed low temper tantrums.